Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 9 lutego 2016 r., sygn. akt I OSK 2691/15 - Mazurek, Przemysław (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The article is a vote approving the position of the Supreme Administrative Court in a judgment that was made on February 9, 2016 in a dispute between the GIODO and the parish priest of the Roman Catholic parish regarding the entry of the apostasy into the parish registers. The approval glossary focuses on emphasizing the importance of autonomy and its importance for the protection and processing of personal data in the Catholic Church and other religious organizations.
Keywords: Catholic Church; autonomy; apostasy; religious association; parish registers; personal data protection; personal data